Diet-Induced Obesity Affects Muscle Regeneration After Murine Blunt Muscle Trauma—A Broad Spectrum Analysis - Xu, Pengfei; Werner, Jens-Uwe; Milerski, Sebastian; Hamp, Carmen M.; Kuzenko, Tatjana; Jähnert, Markus; Gottmann, Pascal; de Roy, Luisa; Warnecke, Daniela; Abaei, Alireza; Palmer, Annette; Huber-Lang, Markus; et al. (Frontiers in Physiology, 2018)
Injury to skeletal muscle affects millions of people worldwide. The underlying regenerative process however, is a very complex mechanism, time-wise highly coordinated, and subdivided in an initial inflammatory, a regenerative and a remodeling phase. Muscle regeneration can be impaired by several factors, among them diet-induced obesity. In order to evaluate if obesity negatively affects healing processes after trauma, we utilized a blunt injury approach to damage the extensor iliotibialis anticus muscle on the left hind limb of obese and normal weight C57BL/6J without showing any significant differences in force input between normal weight and obese mice. Magnetic resonance imaging of the injury and regeneration process revealed edema formation and hemorrhage exudate in muscle tissue of normal weight and obese mice. In addition, morphological analysis of physiological changes revealed tissue necrosis, immune cell infiltration, extracellular matrix remodeling and fibrosis formation in the damaged muscle tissue. Regeneration was delayed in muscles of obese mice, with a higher incidence of fibrosis formation due to hampered expression levels of genes involved in extracellular matrix organization. Furthermore, a detailed molecular fingerprint in different stages of muscle regeneration underlined a delay or even lack of a regenerative response to injury in obese mice. A time-lapse heatmap determined 81 differentially expressed genes with at least three hits in our model at all time points, suggesting key candidates with a high impact on muscle regeneration. Pathway analysis of the differentially expressed genes revealed five pathways with a high confidence level: myeloid leukocyte migration, regulation of tumor necrosis factor production, CD4-positive, alpha-beta T cell differentiation, extracellular matrix organization, and toll-like receptor signaling. Moreover, changes in complement-, Wnt-, and satellite cell-related genes were found to be impaired in obese animals after trauma. Furthermore, histological satellite cell evaluation showed lower satellite cell numbers in the obese model upon injury. Ankrd1, C3ar1, Ccl8, Mpeg1, and Myog expression levels were also verified by qPCR. In summary, increased fibrosis formation, the reduction of Pax7+ satellite cells as well as specific changes in gene expression and signaling pathways could explain the delay of tissue regeneration in obese mice post trauma.